Deep Eutectic Solvents for the Self-Assembly of Gold Nanoparticles: A SAXS, UV–Vis, and TEM Investigation - Raghuwanshi, Vikram Singh; Ochmann, Miguel; Hoell, Armin; Polzer, Frank; Rademann, Klaus (Langmuir, 2014)
In this work, we report the formation and growth mechanisms of gold nanoparticles (AuNPs) in eco-friendly deep eutectic solvents (DES; choline chloride and urea). AuNPs are synthesized on the DES surface via a low-energy sputter deposition method. Detailed small angle X-ray scattering (SAXS), UV–Vis, and cryogenic transmission electron microscopy (cryo-TEM) investigations show the formation of AuNPs of 5 nm diameter. Data analysis reveals that for a prolonged gold-sputtering time there is no change in the size of the particles. Only the concentration of AuNPs increases linearly in time. More surprisingly, the self-assembly of AuNPs into a first and second shell ordered system is observed directly by in situ SAXS for prolonged gold-sputtering times. The self-assembly mechanism is explained by the templating nature of DES combined with the equilibrium between specific physical interaction forces between the AuNPs. A disulfide-based stabilizer, bis((2-mercaptoethyl)trimethylammonium) disulfide dichloride, was applied to suppress the self-assembly. Moreover, the stabilizer even reverses the self-assembled or agglomerated AuNPs back to stable 5 nm individual particles as directly evidenced by UV–Vis. The template behavior of DES is compared to that of nontemplating solvent castor oil. Our results will also pave the way to understand and control the self-assembly of metallic and bimetallic nanoparticles.